2021
DOI: 10.1186/s13195-021-00820-9
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in adults with dementia: clinical features and risk factors of mortality—a clinical cohort study on 125 patients

Abstract: Background There is limited evidence on the characteristics and outcome of patients with dementia hospitalised for novel coronavirus infection (COVID-19). Method We conducted a prospective study in 2 gerontologic COVID units in Paris, France, from March 14, 2020, to May 7, 2020. Patients with dementia hospitalised for confirmed COVID-19 infection were systematically enrolled. A binary logistic regression analysis was performed to identify factors a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 37 publications
2
20
0
Order By: Relevance
“…Although the reasons underlying this association have not been identified, 2 persistent chronic inflammation in diabetes combined with poor control of blood glucose levels during the COVID-19 illness and combined comorbidities of diabetes in itself can affect the prognosis of COVID-19 in patients with diabetes. 33 Some studies showed that patients with dementia, especially those living in care facilities, had an increased risk of COVID-19 and COVID-19-related mortality, 34 35 36 consistent with our findings. Living in care facilities favors the rapid spread of COVID-19 due to the increased likelihood of exposure to the virus in a closed environment, and furthermore, patients with dementia tend to have other underlying comorbidities.…”
Section: Discussionsupporting
confidence: 89%
“…Although the reasons underlying this association have not been identified, 2 persistent chronic inflammation in diabetes combined with poor control of blood glucose levels during the COVID-19 illness and combined comorbidities of diabetes in itself can affect the prognosis of COVID-19 in patients with diabetes. 33 Some studies showed that patients with dementia, especially those living in care facilities, had an increased risk of COVID-19 and COVID-19-related mortality, 34 35 36 consistent with our findings. Living in care facilities favors the rapid spread of COVID-19 due to the increased likelihood of exposure to the virus in a closed environment, and furthermore, patients with dementia tend to have other underlying comorbidities.…”
Section: Discussionsupporting
confidence: 89%
“…A significantly increased risk for COVID-19 and an association with severe outcomes of the pathology have been observed in patients with dementia, including AD [76,77]. On the other hand, neuronal injury and glial activation have been reported in patients with moderate to severe COVID-19 with or without dementia [78].…”
Section: Dementiamentioning
confidence: 99%
“…Dementia was found to be one of the strongest risk factors for COVID-19 and associated with a higher mortality [ 126 , 127 , 128 , 129 , 130 ]. Apparently, patients with dementia have difficulties in following hygiene rules, mask requirements, behavioral instructions and distancing rules due to cognitive deficits [ 124 , 131 ].…”
Section: Chaptermentioning
confidence: 99%
“…Dementia patients frequently live in nursing homes where a higher risk for infection with the virus was present in many areas [ 124 ]. COVID-19 disease in dementia patients often appeared atypical presenting foremost with delirium/confusion and few infectious symptoms [ 129 , 132 ]. Confusion and mood and behavioral disturbances persisted in 19.2% of survivors [ 129 ].…”
Section: Chaptermentioning
confidence: 99%
See 1 more Smart Citation